A comparative study of ionothermal treatment of rice straw using triflate and acetate-based ionic liquids - K.J. Jisha; Sunita Rajamani; Dharmendra Singh; Gyanendra Sharma; Ramesh L. Gardas (Journal of Ionic Liquids, 2022)
Ionic liquids (ILs) have found applications in the pretreatment of waste lignocellulosic biomass by interacting with the carbohydrate molecules present in the biomass materials. Pretreatment is essential before biomass conversion into valuable chemicals, fuels, and many other value-added products. This comparative study mainly focused on the pretreatment ability of four ILs having acetate or triflate as a common anion with different cations. Among various studied ILs, diazabicyclo[5.4.0]undec-7-ene (DBU)-based acidic ionic liquid when used as a dual solvocatalyst showed significant structural modifications of the rice straw (RS) sample, through C6-O bond breakage assisted by the tertiary nitrogen in DBU cation. Structural modifications due to the pretreatment were confirmed through SEM, PXRD, and FTIR analysis. The elemental analysis confirmed that carbon content in original RS is reduced to 29% and 20% upon ionothermal treatment of RS with IL at 90 °C and 120 °C, respectively. Additionally, TGA indicated that further pyrolysis could be easier with the pretreated rice straw yielding biochar up to 9% thereby reducing wastes. Conversion of RS was found to be 60% which reduced marginally to 50% after three cycles of recycling the IL. The findings of this work provide the proof of concept that studied IL with high thermal stability and recyclability should act as a potential solvocatalyst in sustainable pretreatment and other biomass applications.